Pengetahuan Lokal Petani dalam Budidaya Tanaman Sayur di Desa Beruk, Kecamatan Jatiyoso, Kabupaten Karanganyar - Sonia Canda Mahdafika Utami; Sapja Anantanyu; Suminah Suminah (AGRITEXTS: Journal of Agricultural Extension, 2023)
Population growth triggers the need for national food to increase, including the need for vegetable crops as a complement to human nutrition. Efforts made by farmers to meet the population’s needs for vegetable crops and a source of income, often have not paid attention to environmental conditions. Beruk Village is one of the villages where the people cultivate vegetables crops on the slopes of the mountains which should be used as a conservation area. This condition certainly requires farmers to always learn and apply appropriate local techniques so as not to harm the surrounding environment. This research aimed to explore the learning process of farmers in obtaining and examining local knowledge in vegetable cultivation. This study used a qualitative approach method with the interactive model analysis techniques of Miles and Huberman. The results showed that local knowledge of local farmers comes from parents/hereditary, local village farmers, and farmers outside the village through oral, experience, trial and error, and observation. The local knowledge includes seeding (garlic, onion, carrot), land processing stages and its frequency, ‘kalenan’ (horizontal drains), ‘kali gondhang’ (vertical drains), ‘plipit’ (the arrangement stones on the edge of ‘larikan’), benefits of spacing, planting time and season, intercropping, benefits of grass in agricultural land, fertilization methods, weeding, thinning, manual irrigation, utilization of agricultural and livestock waste, as well as method, age, and yield of harvest. The local agricultural tools used are hoe, crowbar, ‘ganco’, garden fork, trowel, sickle, bucket, sack, ‘lanjaran’, and its binder from natural material.